Long term survival after heart transplantation for doxorubicin induced cardiomyopathy. Issue 8 (August 1991) - Aricò, M; Pedroni, E; Nespoli, L; Viganò, M; Porta, F; Burgio, G R
Abstract : A 10 year old child developed severe cardiomyopathy after combined, multicycle chemotherapy for Ewing's sarcoma and was treated by heart transplantation with good results. Long term azathioprine and cyclosporin caused only mild impairment of immune function and there were no recurrent infections, local recurrences of the tumour, or distant metastases.